The effect of various anesthesia techniques on changes in leukocyte types - Handayani, Rahmaya Nova; Suandika, Made; Muti, Refa Teja; Yantoro, Awal Tunis (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2024)
Abstract Background: Surgery and anesthesia can affect the immune and neuroendocrine systems which can cause the release of hormones and cytokines as a result of changes in the body's physiological responses. Neuroendocrine pathways to the immune system related to stress responses due to surgery. surgery and a decrease in the number of T lymphocytes causes a shift in the balance between immunosuppressive regulatory T lymphocytes and immune-triggering T helper and cytotoxic T cells in a predominance of regulatory T cells. Apart from causing a decrease in the number of T lymphocytes, it also causes suppression of NK cells and an increase in the number of neutrophils. Research purposes determine the effect of various anesthetic techniques on changes in leukocyte count levels. Method: This research is a type of experimental research with a pre-pos test group design approach. The samples for this study were taken from patients undergoing surgery and anesthesia with inclusion criteria: age 17-65 years, ASA 1-2, no infectious diseases. The sample size is the sampling technique is Consecutive sampling. Sample measurements were taken from venous blood before and after surgery and anesthesia. The parameters measured are leukocyte counts which include leukocytes, basophils, neutrophils, monocytes and lymphocytes. Blood samples were taken before surgery and anesthesia, and 2 hours after surgery and anesthesia using a hematology analyzer. The analytical tests used are the parametric dependent test (paired T-test) or the non-parametric Wilcoxon test and the independent test. Results: There is a significant difference in the count of leukocyte types between general anesthesia and regional anesthesia Conclusion: General anesthesia can increase leukocyte counts significantly compared to regional anesthesia, but eosinophils are not significant in both groups